Exploring barriers and perceptions to walking and cycling in Nairobi metropolitan area - Basil, Paschalin; Nyachieo, Gladys (Frontiers in Sustainable Cities, 2023)
Walking and cycling as a form of active travel offers an opportunity for individuals to become more active and exercise while performing a functional journey. Notwithstanding, the large percentage of the population, relying on non-motorized transport walking and cycling has not been prioritized. Pedestrian and bicycle friendly city infrastructure is rare and when it exists it is a poor state or not connecting to the main transport system. At a time when health challenges such as obesity and other non-communicable diseases are on rise, walking and cycling would provide a window of opportunity and potential to provide exercise and therefore improve the general health of the population. According to the African Commute (2018) more than 75 percent of total daily trips made by Africa’s poor are by walking, compared 45 percent by the more affluent. When the poor use motorized transport, most of them rely on public transport or motorcycle taxis. Walking and cycling are more than low-carbon modes of transport that enhance urban quality and facilitate social cohesion (United Nations, 2019). In addition, their benefits include reductions in energy use, carbon emissions and traffic congestion. A number of studies have identified gaps in NMT infrastructure, described the inaccessible nature of the NMT network, lack of integration with the other modes of transport, and highlighted the issues of enforcement of laws designed to protect pedestrians and cyclists (Mitullah and Makajuma 2009; Mitullah and Opiyo 2017; Ogendi et al 2013). However, few studies have addressed the existing perceptions and barriers to walking and cycling. This paper will explore perceptions and barriers to walking and cycling in selected high and low-income areas in Nairobi City.